ELECTRICAL BEHAVIOUR OF W-TYPE BaxCo3-xFe16O27 HEXAGONAL FERRITES - Rana, Mazhar U.; Islam, M. U.; Butt, Bilal A.; Abbas, T.; Chaudhry, M. Ashraf; Niazi, Shahida B. (Journal of Research (Science), 2001)
A series of BaxCo3-xFe16O27 hexagonal ferrites with x = 0.5, 1.0, 1.5, 2.0 and 2.5, were prepared using co-precipitation method. The X-ray diffraction analysis of the samples reveals that the crystal structure is hexagonal. Electrical resistivity was measured by two-probe method. The results of temperature dependence on dc electrical resistivity measured in the temperature range 13 to 200°C indicate semi-conducting behaviour of these ferrites. The resistivity and activation energy both increase with the increasing Ba concentrations in all samples.